2016
DOI: 10.1257/aer.p20161050
|View full text |Cite
|
Sign up to set email alerts
|

Declining Business Dynamism: What We Know and the Way Forward

Abstract: A growing body of evidence indicates that the U.S. economy has become less dynamic in recent years. This trend is evident in declining rates of gross job and worker flows as well as declining rates of entrepreneurship and young firm activity, and the trend is pervasive across industries, regions, and firm size classes. We describe the evidence on these changes in the U.S. economy by reviewing existing research. We then describe new empirical facts about the relationship between establishment-level productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(107 citation statements)
references
References 13 publications
(18 reference statements)
5
99
1
2
Order By: Relevance
“…He interpreted such a situation as a symptom of structural deficiency of demand mirrored by the excess savings in corporate sector (Summers, 2014). Empirical research confirmed that the aging population (Gagnon et al, 2016) and declining business dynamism (Decker et al, 2016) have been lowering the rate of economic growth after the Great Recession.…”
Section: Discussionmentioning
confidence: 99%
“…He interpreted such a situation as a symptom of structural deficiency of demand mirrored by the excess savings in corporate sector (Summers, 2014). Empirical research confirmed that the aging population (Gagnon et al, 2016) and declining business dynamism (Decker et al, 2016) have been lowering the rate of economic growth after the Great Recession.…”
Section: Discussionmentioning
confidence: 99%
“…3 Both exit and entry rates are on a slight downward trend over the sample, which might be related to an overall decline in business dynamism as documented in Pugsley and Sahin (2014) and Decker et al (2016). The long-run importance of the decline in export business dynamism remains an open question that we leave for future research.…”
Section: Regression Evidencementioning
confidence: 95%
“…As stressed by several studies, most notably Decker, et al (2014Decker, et al ( , 2016a, there has been a notable decline in U.S. business creation that predates the Great Recession. More recent papers have studied some of the macroeconomic ramifications of the slowdown in business entry.…”
Section: Financial Regulation and Business Formationmentioning
confidence: 99%